2018
DOI: 10.1177/0954410018796988
|View full text |Cite
|
Sign up to set email alerts
|

Localized micro-discharges group dielectric barrier discharge vortex generators: Disturbances source for active transition control

Abstract: In this study, a new type of dielectric barrier discharge plasma actuator for boundary layer control, based on the controllable inhomogeneity of the discharge along the exposed electrode, is developed. The structure of the flow, generated by the isolated groups of microdischarges, was studied in detail in quiescent conditions. In the two-dimensional laminar boundary layer, the flow structure downstream of the actuator was studied for various sweep angles of the electrode. The equivalent model of the actuator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Он состоял из внешнего коронирующего электрода (алюминиевая фольга шириной 23,5 мм, длиной 380 мм и толщиной вместе с клеящим слоем 15 мкм), наклеенного на керамическую (оксид алюминия) пластину толщиной 1 мм, под которой размещался секционированный ответный электрод. Конструкция актуатора подробнее описана в [7]. В большинстве измерений ДБР-актуатор питался синусоидальным напряжением амплитудой 2,5 кВ и частотой 65 кГц.…”
Section: методика экспериментовunclassified
“…Он состоял из внешнего коронирующего электрода (алюминиевая фольга шириной 23,5 мм, длиной 380 мм и толщиной вместе с клеящим слоем 15 мкм), наклеенного на керамическую (оксид алюминия) пластину толщиной 1 мм, под которой размещался секционированный ответный электрод. Конструкция актуатора подробнее описана в [7]. В большинстве измерений ДБР-актуатор питался синусоидальным напряжением амплитудой 2,5 кВ и частотой 65 кГц.…”
Section: методика экспериментовunclassified
“…3 The application of an accurate electronic force balance to measure the plasma-induced force has been demonstrated too. 4 The effects of plasma actuator on the fluid in the vicinity of the electrodes are further measured by means of electrical voltage and light emission measurement, 5,6 smoke flow visualizations, 7,8 hot-wire probe, 9,10 wall pressure measurement, 11,12 particle image velocimetry (PIV), 11,[13][14][15][16][17] laser Doppler velocimetry (LDV), 15 laser induced fluorescence (LIF), 18 and Schlieren techniques 19,20 to name a few. Kotsonis 21 provides a comprehensive review of experimental studies on plasma actuators using a variety of diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
“…This work describes the results of development and testing of the plasma actuator, based on the group of microdischarges (MD) in DBD, localized by sectioning the actuator buried electrode. The concept itself was independently studied by several groups in the attempts to develop the virtual roughness elements to control the cross-flow instability [7,14,15]. The detailed analysis of the flow structure, generated by an isolated MD group, can be found in [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The concept itself was independently studied by several groups in the attempts to develop the virtual roughness elements to control the cross-flow instability [7,14,15]. The detailed analysis of the flow structure, generated by an isolated MD group, can be found in [14,15]. It is shown that a key structure formed downstream of the spanwise limited discharge region is a pair of counter-rotating longitudinal vortices, localized near the wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation